Evaluation of the Implementation of the Independent Curriculum at SMP Negeri 8 Ambon Using the Discrepancy Model - Flawelna Falerery Pesulima; Daniel H. F. Manongga; Yari Dwikurnaningsih (Greenation Research & Yayasan Global Resarch National, 2026)
The curriculum is a crucial component in education that needs to be continuously updated to keep pace with current developments. Curriculum changes help ensure that the education provided not only meets current standards but also supports the holistic development of students' skills and character. This evaluation study uses the Discrepancy Model to assess differences between actual conditions and established standards. This study aims to analyze the design, installation, process, and results of the Independent Curriculum implementation at SMP Negeri 8 Ambon. The method used is an evaluative method with a qualitative descriptive approach. This study was conducted at SMP Negeri 8 Ambon. The research subjects were the principal, the Deputy Head of Curriculum, teachers, and students. Three data collection techniques were used: interviews, observation, and document studies. Data validation used source and technique triangulation, while data analysis followed the Miles and Huberman model. The results of the study show that the Curriculum Design, Curriculum Implementation, Installation, and Curriculum Results are in accordance with the standards set out in the Minister of Education, Culture, Research and Technology Regulation Number 12 of 2024 regarding the implementation of the Independent Curriculum in educational institutions.